Biochemical and molecular analysis of mucopolysaccharidoses in Turkey - Emre, Serap; Terzioğlu, Mügen; Coşkun, Turgay; Tokatlı, Ayşegül; Özalp, İmran and Müller, Vivien and Hopwood, John (The Turkish Journal of Pediatrics, 2002)
The mucopolysaccharidoses (MPSs) are a family of heritable disorders caused by deficiency of lysosomal enzymes needed to degrade glycosaminoglycans (GAGs). The undegraded or partially degraded GAGs are stored in lysosomes and/or excreted in urine. In our study, 118 patients seen over the past 20 years and suspected to have lysosomal storage disorders (LSDs) were subjected to clinical and biochemical analysis at Hacettepe University Children’s Hospital. We analyzed urine and blood samples from 42 patients given a clinical MPS diagnosis. Using urine screening technique, we were able to show that 34 of the 42 patients had MPS condition. Further analysis of eight patients with normal urine MPS patterns revealed four patients as likely to have α-mannosidosis, fucosidosis, sialidosis, and aspartylglucosaminuria (one each). Four patients had normal oligosaccharide patterns. We were able to clearly identify 4 MPS I, 2 MPS II, 5 MPS IIIA, 8 MPS IIIB, 11 MPS IVA, 3 MPS VI, and 1 MPS IIIC patients. These results provided biochemical diagnosis for these 34 patients, and clearly show that Turkey has a higher incidence of MPS IVA, IIIB, and IIIA than of previously suspected MPS types. Molecular analysis of four MPS I patients revealed three polymorphisms which have been previously reported (A314, T388, and A461T). In MPS II patients, mutation analysis identified one previously detected (R172X) and one novel mutation (W109C).